2004
DOI: 10.1086/420733
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Recombination of N2H+: Evidence for Fracture of the N—N Bond

Abstract: Branching ratios and absolute cross sections have been measured for the dissociative recombination of N 2 H + using the CRYRING ion storage ring. It has been found that the channel N 2 H + + e À ! N 2 + H accounts for only 36% of the total reaction and that the branching into the other exoergic pathway, N 2 H + + e À ! NH + N, consequently amounts to 64%. The cross section of the reaction could be fitted by the expression ¼ (2:4 AE 0:4) ; 10 À16 E À1:04AE0:02 cm 2 , which leads to a thermal reaction rate of k(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 40 publications
5
91
3
Order By: Relevance
“…Figure A.2 shows the o:p ratio for NH 2 assuming equilibrium at a single temperature for all levels. dissociative recombination (DR) of the nitrogen bearing cations N 2 H + , NH + 2 , and NH + 4 : -The DR of N 2 H + has been determined experimentally using both flowing afterglow (FA, see Adams et al 1991) and storage ring (SR) techniques (Geppert et al 2004), leading to controversial results concerning the branching ratios (BR) of the two channels N 2 + H and NH + N. Thus, in contrast to the FA results that established the major product as N 2 + H with a BR ≈100%, Geppert et al (2004) found this channel to account for only 36% of the total reaction. The most recent FA and SR measurements (Molek et al 2007;Adams et al 2009), however, have confirmed the earlier FA results that the DR of N 2 H + should lead predominantly to N 2 + H with a BR ≈90−100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure A.2 shows the o:p ratio for NH 2 assuming equilibrium at a single temperature for all levels. dissociative recombination (DR) of the nitrogen bearing cations N 2 H + , NH + 2 , and NH + 4 : -The DR of N 2 H + has been determined experimentally using both flowing afterglow (FA, see Adams et al 1991) and storage ring (SR) techniques (Geppert et al 2004), leading to controversial results concerning the branching ratios (BR) of the two channels N 2 + H and NH + N. Thus, in contrast to the FA results that established the major product as N 2 + H with a BR ≈100%, Geppert et al (2004) found this channel to account for only 36% of the total reaction. The most recent FA and SR measurements (Molek et al 2007;Adams et al 2009), however, have confirmed the earlier FA results that the DR of N 2 H + should lead predominantly to N 2 + H with a BR ≈90−100%.…”
Section: Discussionmentioning
confidence: 99%
“…For the total rate Molek et al (2007) , (c) Thomas et al (2005) , (d) Öjekull et al (2004). coefficient, we adopted the (temperature dependent) expression of Geppert et al (2004), as in the osu.09.2008 network.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements of Adams et al [4] in 1990 indicated that the branching ratios in the dissociative recombination process strongly favor the N 2 + H channel. However, in 2004 Geppert et al [5] reported measurements that the branching ratio to the NH + N channel was dominant. This unexpected result cast doubt on the assumptions mentioned above and motivated additional experimental and theoretical work.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…17]. The chemical model is based on the model of Rodgers & Charnley [60], and has been updated to incorporate recent laboratory measurements of the dissociative recombination channels for several ions, including CH 3 OH + 2 [44,61,62,63,64]. The initial molecular abundances in the newly-formed clump are determined by those in the interclump medium, which are themselves controlled by both (i) the chemistry in these regions, and (ii) whether the material previously passed through a dense phase.…”
Section: Chemical Modelmentioning
confidence: 99%